Surface architecture - Leatherbarrow, David (MIT Press, 2002)
Visually, many contemporary buildings either reflect their systems of production or recollect earlier styles and motifs. This text explores ways that design can take advantage of production methods so that architecture is neither independent of nor dominated by technology.